Impact of women on corporate boards of directors on product quality - Dorota Korenkiewicz; Wolfgang Maennig (Journal of Management and Governance, 2023)
We analyze the impact of women on corporate boards of directors on product quality. We innovate firstly by integrating the broad but fragmented research on the topic, offering a first simultaneously testing of a larger set of variables identified to be significant in earlier studies. Second, we add alternative indicators of female representation in board of directors as a potential determinant of product quality. Third, we use evaluation scores of goods by the nonprofit foundation "Stiftung Warentest" as a quality indicator, thus adding to a regionally diversified evidence. We find a significant positive effect of female board directors on product quality.
Keywords: C30; L21; L25; C13; J16; 650; Gender equality; Women ratio; Women on boards of directors; Product quality; Product reliability; Consumer reports